The Biomechanical Investigation of Osseointegration Levels in Titanium Implants Simultaniously Placed with Different Bone Grafts - Guler, R.; Dundar, S.; Bozoglan, A.; Ozcan, E. c; Ozupek, M. f; Acikan, I; Bingul, M. b (Wolters Kluwer Medknow Publications, 2024)
Background:Dental implant-supported prostheses have been scientifically accepted and have been a common treatment choice in the case reconstructing of partial or total tooth loss. In additon, bone grafts (alloplast, xsenograft, allograft) are frequently used in implant and sinus lift surgical procedures. Aim:The aim of this study is to investigate the bone-implant osseointegration levels of titanium implants simultaniously placed with different bone grafts. Materials and Methods:In the study, 32 female S. Dawley rats were divided into four groups. In the control group (n = 8), turned surface implants with a 2.5 mm diameter and a 4 mm length were placed in the tibia of the rats without the use of a graft material. In the experimental groups, bone cavities were opened in the tibias of the rats and a synthetic (alloplast) graft (n = 8), human allograft (n = 8), and bovine xsenograft (n = 8) were placed simultaniously with a 2.5 mm diameter and a 4 mm length turned surface titanium implants. The cavities in the experimental groups were opened with a 4 mm diameter and a 5 mm length. After 8 weeks of recovery, all rats were sacrificed at the end of the experimental period. The implants and surrounding bone tissue were removed. The removed tissue was subjected to biomechanical analysis in order to evaluate bone-implant osseointegration and peri-implant new bone formation. The Kolmogorov-Smirnov test, Kruskal-Wallis test, and Mann-Whitney U-test were used in the study. Significance was evaluated at the P < 0.05 level. Results:In the biomechanical analyses, it was determined that there was no statistically significant difference between the control group and the other three groups in which different graft materials were applied in terms of bone-implant osseointegration (P > 0.05). In other words, in the biomechanical analyses, no statistical difference was found between any of the groups. Conclusions:As a result of this study, it can be thought that different graft materials can be successfully used in peri-implant-guided bone regeneration and may be an alternative to autogenous grafts.
Keywords: Bone grafts; bone-implant connection; bone-implant contact; guided bone regeneration; osseointegration; tissue regeneration